1996
DOI: 10.1086/133825
|View full text |Cite
|
Sign up to set email alerts
|

A Database for Galaxy Evolution Modeling

Abstract: This paper represents a collective effort to provide an extensive electronic database useful for the interpretation of the spectra and evolution of galaxies. A broad variety of empirical and theoretical data are discussed here, and the data are made fully available in the AAS CD-ROM Series, Vo. 7. Several empirical stellar libraries are part of this database. They cover the ultraviolet spectral range observed with IUE, optical data from different ground-based telescopes, and ground-based infrared data. Spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(108 citation statements)
references
References 64 publications
3
105
0
Order By: Relevance
“…We must use either synthetic spectra or spectra taken through other spectroscopic configurations and transform these to our system. We use templates from two sources: the Coudé Feed Spectral Library at KPNO (Leitherer et al 1996), and the stellar templates observed by Kobulnicky & Gebhardt (2000). The KPNO library consists of 684 stars having a broad range of spectral types, with 1.8 Å FWHM resolution.…”
Section: Kinematic Propertiesmentioning
confidence: 99%
“…We must use either synthetic spectra or spectra taken through other spectroscopic configurations and transform these to our system. We use templates from two sources: the Coudé Feed Spectral Library at KPNO (Leitherer et al 1996), and the stellar templates observed by Kobulnicky & Gebhardt (2000). The KPNO library consists of 684 stars having a broad range of spectral types, with 1.8 Å FWHM resolution.…”
Section: Kinematic Propertiesmentioning
confidence: 99%
“…In our study we adopt the isochrones by Tantalo (1998) (anticipated in the data base for galaxy evolution models by Leitherer et al 1996). The underlying stellar models are those of the Padova Library.…”
Section: Libraries Of Stellar Models and Stellar Spectramentioning
confidence: 99%
“…The templates also extend further to the UV and near-IR domains, which can be used as additional constraints in the analysis. A detailed description of these templates is given by Bica and collaborators in°4.1 of Leitherer et al (1996). To represent a 3 Myr stellar population, we adopt the integrated spectrum of 30 Doradus (BAS94, Bica & Alloin 1986 In the old stellar population template, typical of elliptical galaxies or of the bulge of spirals, the main absorption features are the Ca II K (j3933) and H (j3970) lines and a blend of absorptions caused by CN, Mg I, Si I, and Fe I.…”
Section: Near-ultraviolet Features and Adopted Templatesmentioning
confidence: 99%